2021
DOI: 10.1038/s41467-021-22612-3
|View full text |Cite
|
Sign up to set email alerts
|

Poly(fluorenyl aryl piperidinium) membranes and ionomers for anion exchange membrane fuel cells

Abstract: Low-cost anion exchange membrane fuel cells have been investigated as a promising alternative to proton exchange membrane fuel cells for the last decade. The major barriers to the viability of anion exchange membrane fuel cells are their unsatisfactory key components—anion exchange ionomers and membranes. Here, we present a series of durable poly(fluorenyl aryl piperidinium) ionomers and membranes where the membranes possess high OH− conductivity of 208 mS cm−1 at 80 °C, low H2 permeability, excellent mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
145
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(156 citation statements)
references
References 54 publications
2
145
0
Order By: Relevance
“…Anion exchange membrane fuel cells (AEMFCs) operating in alkaline media are a new type of SPFC technology that attempts to solve the high-cost issues associated with proton exchange membrane fuel cells (PEMFCs), which rely on platinum-group-metal (PGM) catalysts to tackle with harsh acid environments. 1–4 That is, AEMFCs provide an attractive option for practical utilization of earth-abundant PGM-free catalysts. However, AEMFCs are faced with many inherent challenges related to alkaline conditions, particularly in terms of power density and durability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anion exchange membrane fuel cells (AEMFCs) operating in alkaline media are a new type of SPFC technology that attempts to solve the high-cost issues associated with proton exchange membrane fuel cells (PEMFCs), which rely on platinum-group-metal (PGM) catalysts to tackle with harsh acid environments. 1–4 That is, AEMFCs provide an attractive option for practical utilization of earth-abundant PGM-free catalysts. However, AEMFCs are faced with many inherent challenges related to alkaline conditions, particularly in terms of power density and durability.…”
Section: Introductionmentioning
confidence: 99%
“…15–19 Four types of cationic groups, quaternary ammonium (QA), imidazolium, phosphonium, and organic–metal cations, have been the main focus in current AEMFC research; however, most of these materials are unstable under alkaline conditions. 4,11,12,20–25 Many degradation reactions have been monitored in these cationic groups, such as nucleophilic substitution, Hofmann degradation, the Ylide reaction, and coordination degradation. 2,4,15 Moreover, many aryl ether polymer backbones (such as polyether-ether-ketone and polysulfone) have been documented to be easily cleaved under alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5 , 6 , 7 , 8 , 9 , 10 ] In the past few years, AEMFCs have made great breakthroughs in achieving high performances with peak power densities (PPDs) now common above 1 W cm –2 (Fuel cell data of recently reported anionomers (also known as anion exchange ionomers, AEIs) or anion exchange membrane (AEMs) for H 2 /O 2 AEMFCs represented in Table S1 , Supporting Information). [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] These studies are gradually narrowing the performance gap with PEMFCs due to the development of AEMs accompanied by high OH − conductivity as well as optimization of catalytic electrode designs and water balance. However, the lack of long‐term AEMFC durabilities, particularly at high temperatures, low humidities, and/or with realistic current density operation, is a critical barrier to adoption into commercial markets (cf.…”
Section: Introductionmentioning
confidence: 99%
“…The MEAs containing PFTFPh-C8-QA and PFTFPh-C10-QA showed almost stable cell voltages up to 140 and 150 h, respectively, at a current density of 200 mA cm À2 . Overall, these results indicated that the AEMs prepared from high molecular weight poly(fluorene-alttetrafluorophenylene), containing longer alky side chain with quaternary ammonium groups in the polymer backbone, exhibited higher dimensional stability and flexibility, while simultaneously producing moderate IEC and ionic conductivity.Most of the studies on the applicability of fluorene polymers asAEMs focused on the use of quaternary ammonium groups, due to their high hydroxide ion conductivity, durability, and feasibility.Recently, development of novel poly(fluorenyl aryl piperidinium) copolymers (as shown in Figure7) for use as AEMs and anion exchange ionomers have been undertaken for their potential application in alkaline fuel cell 40,51. Chen et al prepared a high molecularF I G U R E 5 Structures of poly(fluorenyl aryl piperidinium) copolymers, having varying degrees of fluorene unit.…”
mentioning
confidence: 99%